Coarse scale cost–utility approach for efficient unequal loss protection - Chen, Yisong; Wang, Guoping; Dong, Shihai (Signal processing. Image communication, 2002)
The framework of unequal loss protection (ULP) is an attractive method for the protection of the embedded image or video data source generated by a scalable coding scheme in the environment of packet switched networks. In this paper, an efficient preprocessing algorithm is presented based on the idea of the coarse scale cost–utility (CSCU) working curve. The experimental results show that the CSCU method significantly improves the efficiency of the ULP assignment framework with substantial memory and computation savings. We believe that the idea of coarse scale operation can also be successfully used in many other applications.